Listening As a Receptive Type of Speech Activity - Boltaeva Durdona Bahodirovna (Genius Journals, 2021)
In the article, there is discussed about listening as a receptive type of speech activity, perception and understanding of a foreign language of an oral message. As well as the difficulties of understanding a foreign language by ear and ways to overcome them, the system of exercises for the formation of listening skills is analyzed in the article
Keywords: Listening; Skills Formation; Difficulty of Understanding; Exercise System